[AR] Fawa'id Istikhdam ChatGPT wa ‘Awa'iquha lada Talabah al-Dirasat al-’Ulya bi Qism al-Lughah al-’Arabiyyah wa Adabiha bi al-Jami'ah al-Islamiyyah al-'Alamiyyah bi Maliziya: Benefits and Barriers of Using ChatGPT Among Postgraduate Students in the Department of Arabic Language and Literature at International Islamic University Malaysia (Afaq Lughawiyyah, 2024)
Although using ChatGPT offers benefits to its users, it also brings potential drawbacks. This study aims to explore the benefits of using ChatGPT among Postgraduate students in the Department of Arabic Language and Literature at International Islamic University Malaysia (IIUM) and to determine the barriers of using ChatGPT among them. The research sample was selected using a cluster sample by using a quantitative descriptive method. This research was conducted on 32 students using a questionnaire that was distributed through Google Form to collect data. Then the researchers analysed the data using Statistical Package for the Social Sciences (SPSS) according to the analysis of the total sum and the mean. The findings of this study showed that the three main benefits of using ChatGPT are helping in brainstorming, helping in translation educational materials into different languages and helping in saving time in completing tasks. In brief, most of the students showed positive attitudes towards the use of ChatGPT and they agreed that it showed many significant benefits than its barriers.